The burden of smoking-related ill health in the UK. Issue 4 (9th June 2009) - Allender, S; Balakrishnan, R; Scarborough, P; Webster, P; Rayner, M
Abstract : Background: Smoking is one of the biggest avoidable causes of morbidity and mortality in the United Kingdom. This paper quantifies the current health and economic burden of smoking in the UK. It provides comparisons with previous studies of the burden of smoking in the UK and with the costs for other chronic disease risk factors. Methods: A systematic literature review to identify previous estimates of National Health Service costs attributable to smoking was undertaken. Information from the World Health Organization's Global Burden of Disease Project and routinely collected mortality data were used to calculate mortality due to smoking in the UK. Population-attributable fractions for smoking-related diseases from the Global Burden of Disease Project were applied to NHS cost data to estimate direct financial costs. Results: Previous studies estimated that smoking costs the NHS about £1.4 billion to £1.7 billion in 1991 and has been responsible for about 100 000 deaths per annum over the past 10 years. This paper estimates that the number of deaths attributable to smoking in 2005 was 109 164 (19% of all deaths, 27% deaths in men and 11% of deaths in women). Smoking was directly responsible for 12% of disability adjusted life years lost in 2002 (15.4% in men; 8.5% in women) and the direct cost to the NHS was £5.2 billion in 2005–6. Conclusion: Smoking is still a considerable public health burden in the UK. Accurately establishing the burden in terms of death, disability and financial costs is important for informing national public health policy.